The Long-Term Effect of Calcium Hydroxide, Calcium-Enriched Mixture Cement and Mineral Trioxide Aggregate on Dentin Strength - Moazami, Fariborz; Sahebi, Safoora; Jamshidi, Davoud; Alavi, Aliasghar (Iranian Endodontic Journal, 2014)
Introduction: Many of highly-alkaline dental materials have some adverse effects on physical properties of dentin. As basic substances, mineral trioxide aggregate (MTA), calcium hydroxide (CH) and the new endodontic material, calcium-enriched mixture (CEM) cement, may adversely affect dentin. The purpose of this in vitro study was to evaluate the effect of long-term application of CEM cement, MTA and CH on flexural strength of bovine dentin. Materials and Methods: Three hundred and twenty bovine dentin samples were divided into 4 groups, which were either exposed to CEM cement, CH, MTA or normal saline (control group). Samples of each group were divided into 4 subgroups which were tested by means of Instron Universal Testing Machine for periods of 7, 30, 180 and 365 days after exposure to the test materials. The required force for sample breakage was recorded. The data were analyzed by the two-way ANOVA and Tukey tests. Results: The mean value of forces to break the samples in CEM cement and CH groups was significantly lower than the control group after 1 month (P<0.05). After 180 days, the samples of CEM cement group retrieved their strength but in MTA and CH groups the time interval weakened the samples. After one year of exposure to CH and MTA, flexural strength of the dentin reduced to 72% and 38.7%, respectively (P<0.05). Yet the flexural strength of samples in CEM cement group did not change significantly compared to control group. Conclusion: Following 365 days of application of experimental materials to bovine dentin, the CEM cement showed an interesting result and the samples in this group reached their initial strength during the first week of the study but the other materials caused a reduction in dentin strength at the end of the study.